Moderate-to-vigorous intensity physical activity among U.S. adolescents before and during the COVID-19 pandemic: Findings from the Adolescent Brain Cognitive Development Study - Cortez, Catherine A.; Yuefan Shao, Iris; Seamans, Marissa J.; Dooley, Erin E.; Pettee Gabriel, Kelley; Nagata, Jason M. (Preventive medicine reports, 2023)
Only 16.1% percent of U.S. adolescents meet the recommendation of at least 60 minutes of moderate-to-vigorous intensity physical activity (MVPA) per day. Studies report declined levels of adolescent MVPA in early stages of the pandemic, but gaps remain in understanding changes beyond the initial three months of the pandemic. This study aims to describe and compare self-reported adolescent MVPA levels at multiple timepoints before and during the COVID-19 pandemic among 11,865 9-11-year-old U.S. adolescents from the Adolescent Brain Cognitive Development (ABCD) Study, including pre-pandemic (September 2016-October 2018), early (May, June, and August 2020), and later (October and December 2020, March 2021) stages of the pandemic. Poisson regression models with robust error variance were used to estimate crude and adjusted prevalence ratios (APRs) of the proportion of adolescents meeting national MVPA guidelines during early and later stages of the pandemic compared to pre-pandemic. The proportion of adolescents meeting MVPA guidelines decreased from pre (16.4%), early (11.0%), and later (4.7%) COVID-19 pandemic timepoints. Adolescent MVPA guideline adherence at early- and later-pandemic stages was 24% lower (APR 0.76, 95% CI 0.62, 0.93) and 68% lower (APR 0.32, 95% CI 0.24, 0.43) than pre-pandemic adherence, respectively. Weekly MVPA duration decreased throughout May 2020 to March 2021 (χ2 = 488.9, p < 0.0001). Study findings build upon existing evidence that the low achievement of national MVPA guidelines before the pandemic became even lower during the pandemic, demonstrating the need to support and improve access to adolescent MVPA opportunities during COVID-19 pandemic recovery efforts and in future pandemics.